Molecular identification of peacock bass (Cichla ocellaris) from the Bedog River, Yogyakarta, Indonesia - SAPTO ANDRIYONO; HIMAWAN AKHMAD; MD. JOBAIDUL ALAM; NINA NURMAULINA DEWI; LAILATUL LUTFIYAH; SUCIYONO SUCIYONO (Society for Indonesian Biodiversity, 2025)
Abstract. Andriyono S, Akhmad H, Alam MJ, Dewi NN, Lutfiyah L, Suciyono. 2025. Molecular identification of peacock bass (Cichla ocellaris) from the Bedog River, Yogyakarta, Indonesia. Biodiversitas 26: 1565-1572. The introduction of non-native fish species can lead to the establishment of invasive species groups that pose environmental threats and contribute to biodiversity loss. The primary aim of this study was the precise molecular identification of specific Cichla spp. from the Bedog River in Yogyakarta. Seven Cichla fish samples were collected from the Bedog River (upstream and downstream area) from August to October 2020 using a fish net. The cytochrome C Oxidase subunit I (COI) gene region serves as the basis for species identification, with comparisons made against the National Center for Biotechnology Information (NCBI) database. In this study, the primers used in PCR were Universal Fish BCL-BCH primers. The PCR results were followed by sequencing using the Sanger platform. Of the seven samples procured from the Bedog River, all unequivocally indicated the presence of the Cichla species, identified explicitly as Cichla ocellaris (99.68-100% similarity to reference NC030272). Furthermore, upon phylogenetic tree construction, these sequences consistently clustered with C. ocellaris and Cichla temensis sequences. Nevertheless, discerning characteristics of the color pattern align more closely with C. ocellaris. The identification of non-native species in the Bedog River underscores the imperative for vigilant monitoring of fish introductions to avert potential harm to indigenous fish populations. The predatory nature of C. ocellaris raises concerns about its capacity to exert pressure on local fish populations, potentially culminating in its invasive establishment—a phenomenon with deleterious implications for tropical fish biodiversity in Indonesia. DNA Barcode applications are essential in supporting the provision of accurate data and in preventing the illegal spread of non-native fish.